2016
DOI: 10.1038/ncomms12369
|View full text |Cite
|
Sign up to set email alerts
|

LTβR controls thymic portal endothelial cells for haematopoietic progenitor cell homing and T-cell regeneration

Abstract: Continuous thymic homing of haematopoietic progenitor cells (HPCs) via the blood is critical for normal T-cell development. However, the nature and the differentiation programme of specialized thymic endothelial cells (ECs) controlling this process remain poorly understood. Here using conditional gene-deficient mice, we find that lymphotoxin beta receptor (LTβR) directly controls thymic ECs to guide HPC homing. Interestingly, T-cell deficiency or conditional ablation of T-cell-engaged LTβR signalling results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 60 publications
8
63
0
Order By: Relevance
“…Consistently, we found that LTα expression is required for the expression of adhesion molecules and chemokines, known to promote T‐cell progenitor entry in the thymus, in stromal cells during BMT. In accordance with our data, it has been recently reported that LTβR regulates at steady state thymus homing by controlling VCAM‐1 and ICAM‐1 on endothelial cells (Lucas et al , ; Shi et al , ). Peripheral T‐cell reconstitution is thus altered in BM‐transplanted LTα −/− mice, which is explained by a diminished thymic export of CD4 + and CD8 + T cells revealed by a weak frequency of recent thymic emigrants.…”
Section: Discussionsupporting
confidence: 93%
“…Consistently, we found that LTα expression is required for the expression of adhesion molecules and chemokines, known to promote T‐cell progenitor entry in the thymus, in stromal cells during BMT. In accordance with our data, it has been recently reported that LTβR regulates at steady state thymus homing by controlling VCAM‐1 and ICAM‐1 on endothelial cells (Lucas et al , ; Shi et al , ). Peripheral T‐cell reconstitution is thus altered in BM‐transplanted LTα −/− mice, which is explained by a diminished thymic export of CD4 + and CD8 + T cells revealed by a weak frequency of recent thymic emigrants.…”
Section: Discussionsupporting
confidence: 93%
“…Given the widespread LTβR expression by multiple thymic stromal cell types ( Fig. 2 A ; Shi et al, 2016 ; Sitnik et al, 2016 ; Cosway et al, 2017 ), any cell type–specific requirements for LTβR during thymus emigration are unknown. To address this, we generated mice lacking LTβR in specific stromal cells.…”
Section: Resultsmentioning
confidence: 99%
“…3 I ), suggesting LTβR controls egress independently of these molecules. Finally, a novel LTβR-dependent Ly6C − CD62P + thymic endothelial subset termed the portal endothelium has been recently identified and linked to regulation of lymphoid progenitor cell entry ( Shi et al, 2016 ). In agreement with these studies, we observed significant loss of Ly6C − CD62P + portal endothelium in LTβR ENDO mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…P-selectin expression is upregulated on EC when TSP cellularity diminishes[17], suggesting a positive feedback loop through which EC recruit TSP as space becomes available. Thymic EC are heterogeneous, and both KitL + EC[18] and P-selectin + Ly6c lo EC[19,20] have been implicated as TSP portals. However, these two candidates differ in expression of genes critical for differentiation of immature thymocytes, such as Cxcl12 and Dll4, leaving open the question of which serves as the true TSP niche.…”
Section: Import Of Hematopoietic Progenitors Into the Thymusmentioning
confidence: 99%